Polar-Twisted, Nano-Modulated Nematics: Form Chirality and Physical Properties - Alexandros G. Vanakaras; Edward T. Samulski; Demetri J. Photinos (Liquids)
Recently, two new polymorphs have been added to the nematic class: the polar-twisted nematic (NPT) in 2016 and the ferroelectric nematic (NF) in 2020. Comprised of achiral molecules, both exhibit local polar ordering and adopt modulated structures, right- and left-handed helical organizations—form chirality—albeit on vastly different dimensional scales; modulations have a ~10 nanometer pitch in the NPT and ~500 nm in the NF. Here, we focus on the structure and symmetries of the NPT phase and the ensuing physical properties. Based on an array of order parameters that fully describe the molecular ordering and the nano-modulations thereof, we present a consistent formulation of the dielectric, optical, surface anchoring, and elasticity properties of the NPT materials. We show that these properties are distinctly different from those associated with an elastically modulated, locally uniaxial, nematic.